The complete chloroplast genome sequence of Altingia excelsa - Dejun Yang; Qiong Qiu; Linhong Xu; Yumei Xu; Yi Wang (Mitochondrial DNA. Part B. Resources, 2020)
The first complete chloroplast genome (cpDNA) sequence of Altingia excelsa was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 160,861 bp in length, contains a large single copy region (LSC) of 89,126 bp and a small single copy region (SSC) of 19,011 bp, which were separated by a pair of inverted repeats (IR) regions of 26,362 bp each. The genome contains 127 genes, including 82 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. Phylogenomic analysis showed that A. excelsa and Liquidambar formosana clustered in a clade in Saxifragales order.